ANALISIS YURIDIS PUTUSAN PENGADILAN TINDAK PIDANA PEMUFAKATAN JAHAT DALAM MELAKUKAN TINDAK PIDANA NARKOTIKA OLEH ANAK - Yelli Sri Wahyuni; Sukmareni; Syaiful Munandar (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2023)
Narcotics Crime has occurred a lot in Indonesia. One of those who commit narcotic crimes is a child. Parents are obliged to fulfill the rights of children so as not to fall into drugs and promiscuity. As is the case with the defendant Fajar Bumi Putra who has been sentenced by the Payakumbuh District Court judge, but the problems and objectives of this study are to analyze 1) The basis for the judge's consideration of the Evil Conspiracy case Number 1/Pid.Sus-Anak/2021/PN-Pyh in imposing a sentence on a child who commits a narcotic crime. 2) The basis in what case is a child who commits a narcotic crime under number 1/Pid.Sus-Anak/2021/PN Pyh regarding Evil conspiracy committed by children is in accordance with the Law.. Based on the results In this study, the authors suggest efforts to prevent narcotics crime, protect children's values ​​and educate children so they don't fall prey to narcotics and promiscuity by judges and law enforcement officials such as public prosecutors.